PENGARUH BRAND TRUST DAN BRAND EQUITY TERHADAP LOYALITAS PELANGGAN TRI DI 3STORE DENPASAR - Hardi Sidarta (Majalah Ilmiah Widyacakra, 2019)
The purpose of this study was to determine the effect of Trust Brand and Brand Equity on Tri customer loyalty at 3Store Denpasar. The data sources used are primary and secondary data. Data analysis techniques used classical assumptions analysis consisting of normality test, heteroscedasticity test, and multicollinearity test, multiple correlation analysis, multiple linear regression analysis, analysis of determination, and statistical tests. The results of the study were obtained from the analysis using a computer program SPSS for Windows ver 22. From the results of the normality test Asymp Sig (2-tailed) amounted to 0.119 which means greater than the significant level of 5% (0.05). This shows that the data used in this study is normally distributed. The results of heteroscedasticity test, namely brand trust (X1) are 0.381 and brand equity (X2) is 0.285. The results of multicolourity test analysis, namely the Variance Inflation Factor VIF value for each variable is 1.001 smaller than 10 (VIF <10), tolerance value on brand trist variables (X1) and problematic brand equity (X2) each has a value of 0.999 is greater than 0.10 (tolerance> 0.10), so there are no multicollinearity problems between these two independent variables. Based on the calculation of the multiple correlation coefficient (R) is 0.556 means that there is a positive or direct relationship between brand trust and brand equity to customer loyalty. The results of multiple linear regression of brand trust (X1) and brand equity (X2) on customer loyalty (Y) are: Y = 5.857 + 0.392X1 - 0.277X2 .. From the test results the coefficient of determination can mean that brand trust and brand equity affect loyalty Tri customers at 3Store Denpasar amounted to 30.9% while the remaining 69.1% were influenced by other variables not discussed in this study. While the Individual Parameter Significance Test (Statistic Test t) is brand trust (X1) has a positive and significant effect with the t-test results of 5.652 and sig 0,000 on customer loyalty variables (Y) and brand equity variables (X2) positively influencing the test results t is 3.282 and sig 0.001 for customer loyalty variable (Y) Tri at 3Store Denpasar.